2016
DOI: 10.1152/japplphysiol.00524.2016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the detailed kinetics of mitochondrial cytochromecoxidase: Catalytic mechanism and nitric oxide inhibition

Abstract: Cytochrome c oxidase (CcO) catalyzes the exothermic reduction of O to HO by using electrons from cytochrome c, and hence plays a crucial role in ATP production. Although details on the enzyme structure and redox centers involved in O reduction have been known, there still remains a considerable ambiguity on its mechanism of action, e.g., the number of sequential electrons donated to O in each catalytic step, the sites of protonation and proton pumping, and nitric oxide (NO) inhibition mechanism. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
(82 reference statements)
0
17
0
1
Order By: Relevance
“…Also, in a rat skeletal muscle study, a twofold increase in the respiratory capacity in white, red, and mixed muscle fibres was attributed to an approximately twofold increase of citrate synthase, cytochrome c , and cytochrome c oxidase . Computational studies confirmed a close relationship among cytochrome c reduced and oxidized concentrations and mitochondrial respiration rate …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Also, in a rat skeletal muscle study, a twofold increase in the respiratory capacity in white, red, and mixed muscle fibres was attributed to an approximately twofold increase of citrate synthase, cytochrome c , and cytochrome c oxidase . Computational studies confirmed a close relationship among cytochrome c reduced and oxidized concentrations and mitochondrial respiration rate …”
Section: Discussionmentioning
confidence: 78%
“…The reduced content of cytochrome c and c 1 found in SSM in comparison to that observed for IFM is consistent with a lower respiration rate of SSM compared to that of IFM. Experimental and computational studies support a strong relationship between cytochrome c content and respiratory capacity. In a rat kidney study from our laboratory, a decrease in oxidative phosphorylation was reported to be related to a reduced cytochrome c content of mitochondria with intact outer membranes .…”
Section: Discussionmentioning
confidence: 79%
“…NO acts as a multisite inhibitor of the mitochondrial ETC. The most sensitive and widely studied target for NO in mitochondria is the terminal enzyme of the ETC, cytochrome c oxidase [9, 23, 24]. NO competes with O 2 at the binuclear Cu B /cytochrome a 3 site.…”
Section: Discussionmentioning
confidence: 99%
“…NO competes with O 2 at the binuclear Cu B /cytochrome a 3 site. This competition with O 2 results in the inhibition of the enzyme, suggesting that NO is an important physiological regulator of mitochondrial oxidative phosphorylation [9, 23, 24]. Reports [25, 26] that the presence of the mitochondrial NOS isoenzyme is a constitutive protein in the mitochondrial inner membrane support a potential physiological role for NO in mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 99%
“…The most important sensitive site to NO is COX, which is the terminal electron acceptor of the respiratory chain and is the enzyme complex that reduces molecular oxygen to H 2 O, helping generate a proton gradient that drives Complex V and ATP synthesis. The kind of NO inhibition is dependent on COX redox state (5254). COX is reduced after receiving electrons from cytochrome c and the reduction of the metals (Fe2+ and Cu+) when molecular oxygen binds to a heme-copper binuclear active site (53).…”
Section: No the Respiratory Chain And Control Of Respirationmentioning
confidence: 99%